Streblus asper attenuates alloxan-induced diabetes in rats and demonstrates antioxidant and cytotoxic effects - M. Oliur Rahman; Ali S. Alqahtani; Sayma Binte Huda; Shah Alam Siddiqui; Omar M. Noman; Fahd Nasr; Md. Abul Hassan; Sheikh Nazrul Islam (Taylor & Francis Group, 2021)
Context Streblus asper Lour. (Moraceae) is used for the treatment of different ailments, including diabetes, and requires scientific validation. Objective The study evaluates antidiabetic effects, antioxidant potential, and cytotoxicity of leaf and bark extracts of S. asper. Materials and methods Antidiabetic effects were assessed by inducing diabetes in Wistar albino rats (n = 5, six groups included 30 rats) by injecting alloxan [0.25 mg/kg body weight (bw)] intraperitoneally, and efficacy of methanol extracts of leaf and bark, and aqueous extract of leaves were evaluated by oral administration of 300 mg/kg bw of extracts for 3 weeks. Glibenclamide (Dibenol™) was used as a control (10 mg/kg bw). Antioxidant properties were examined by DPPH free radical scavenging activity, and cytotoxicity was investigated using a brine shrimp lethality assay. Results Methanol extracts of leaves and bark, and the aqueous extract of leaves of S. asper, caused significant reductions in blood glucose levels in diabetic rats of 36.83, 70.33, and 52.71%, respectively, after 21 days of treatment. IC50 values in DPPH radical scavenging assessment for those extracts were 58.92, 88.54, and 111.36 µg/mL, respectively. LC50 values for brine shrimp lethality for the extracts were 173.80, 32.36, and 3235.9 µg/mL, respectively. Discussion and conclusions The methanol bark extract of S. asper showed significant antidiabetic activity. This study will significantly contribute to establishing the plant as an alternative medicinal resource for rural populations of Bangladesh and provides an opportunity for further research to identify the primary active compound(s) and establish new drug candidates.